Making and working Egyptian blue – a review of the archaeological evidence. (May 2023) - Kovalev, I.; Rodler, A.S.; Brøns, C.; Rehren, Th.
Abstract: As the earliest artificial pigment, Egyptian blue has a millennia-long history of production, processing/working, and use. This paper offers a review of the published archaeological evidence for Egyptian blue production, aiming to identify common and potentially diagnostic criteria for each process step to aid future identification and interpretation of Egyptian blue workshops sensu lato . We identify systematic differences in the production evidence between Late Bronze Age and Hellenistic to Late Roman sites, respectively, and propose a model to distinguish between primary production and secondary/artistic processing of Egyptian blue. Finally, we note the absence of direct evidence for the production and processing of Egyptian blue for much of the known period of its use. Highlights: Egyptian blue production required raw materials, temperature control and crucibles. The structure of production includes primary production sites and secondary processing workshops. Criteria for primary production and secondary processing identification are proposed. Crucibles are the major indicator for primary production identification.